Redox-Modulating Capacity and Effect of Ethyl Acetate Roots and Aerial Parts Extracts from Geum urbanum L. on the Phenotype Inhibition of the Pseudomonas aeruginosa Las/RhI Quorum Sensing System - Lyudmila Dimitrova; Milka Mileva; Almira Georgieva; Elina Tzvetanova; Milena Popova; Vassya Bankova; Hristo Najdenski (Plants)
Pseudomonas aeruginosa is an opportunistic pathogen that causes nosocomial infections of the urinary tract, upper respiratory tract, gastrointestinal tract, central nervous system, etc. It is possible to develop bacteremia and sepsis in immunocompromised patients. A major problem in treatment is the development of antibiotic resistance. Therefore, new preparations of natural origin are sought, such as plant extracts, which are phytocomplexes and to which it is practically impossible to develop resistance. Geum urbanum L. (Rosacea) is a perennial herb known for many biological properties. This study aimed to investigate the redox-modulating capacity and effect of ethyl acetate (EtOAc) extracts from roots (EtOAcR) and aerial parts (EtOAcAP) of the Bulgarian plant on the phenotype inhibition of the P. aeruginosa Las/RhI quorum sensing (QS) system, which primarily determines drug resistance in pathogenic bacteria, including biofilm formation, motility, and pigment production. We performed QS assays to account for the effects of the two EtOAc extracts. At sub-minimal inhibitory concentrations (sub-MICs) ranging from 1.56 to 6.25 mg/mL, the biofilm formation was inhibited 85% and 84% by EtOAcR and 62% and 39% by EtOAcAP extracts, respectively. At the same sub-MICs, the pyocyanin synthesis was inhibited by 17–27% after treatment with EtOAcAP and 26–30% with EtOAcR extracts. The motility was fully inhibited at 3.12 mg/mL and 6.25 mg/mL (sub-MICs). We investigated the inhibitory potential of lasI, lasR, rhiI, and rhiR gene expression in biofilm and pyocyanin probes with the PCR method. Interestingly, the genes were inhibited by two extracts at 3.12 mg/mL and 6.25 mg/mL. Antiradical studies, assessed by DPPH, CUPRAC, and ABTS radical scavenging methods and superoxide anion inhibition showed that EtOAcAP extract has effective antioxidant capacity. These results could help in the development of new phytocomplexes that could be applied as biocontrol agents to inhibit the phenotype of the P. aeruginosa QS system and other antibiotic-resistant pathogens.